2007
DOI: 10.1016/j.buildenv.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic airflow simulation within an isolation room

Abstract: In many hospitals, isolation rooms are used to contain patients who are highly infectious, and the spread of air and bacteria within the isolation room is closely relates to room air distribution. This article uses the computational fluid dynamics (CFD) method to investigate the effects of a moving person and the opening and closing of a sliding door on room air distribution, including velocity, pressure and contaminant fields. Dynamic meshes are employed to simulate the movement of the walking person and slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 7 publications
3
57
0
Order By: Relevance
“…The negative values assumed by the x-velocity component depend by the chosen orientation of the Cartesian system of coordinates, and well underline the air flow direction when the door is opening. This effect, caused by the mixing between the air flow inside the room with that at the ceiling supply diffuser and the outside flow, is confirmed by recent studies [32]. The effect of temporal or extended period of door opening but also of surgical staff movements, that can obstruct the ventilation system efficiency, widely explained in the above cited papers, can be compared with our simulation results connected to relative velocity and pressure difference variations.…”
Section: Implemented Procedures For "Moving Objects" Simulationsupporting
confidence: 87%
See 1 more Smart Citation
“…The negative values assumed by the x-velocity component depend by the chosen orientation of the Cartesian system of coordinates, and well underline the air flow direction when the door is opening. This effect, caused by the mixing between the air flow inside the room with that at the ceiling supply diffuser and the outside flow, is confirmed by recent studies [32]. The effect of temporal or extended period of door opening but also of surgical staff movements, that can obstruct the ventilation system efficiency, widely explained in the above cited papers, can be compared with our simulation results connected to relative velocity and pressure difference variations.…”
Section: Implemented Procedures For "Moving Objects" Simulationsupporting
confidence: 87%
“…In this last paper, the influence of the dooropening procedure was ignored since the door of the operating room is a sliding one and in particular the effect of people crossing with and without a stretcher is disregarded. Some authors used numerical [32] or experimental [33] approaches to investigate the effects of one moving person or the movement of a sliding door on the air distribution, including air velocity and pressure field but also CO2 contaminant distribution, within generic ventilated or specific negative pressure isolation rooms [34]. Among the numerical based studies, simulation of object or person movements has been handled directly or indirectly [35].…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental [12][13][14][15][16] and numerical methods [5,9,10,[17][18][19][20][21][22] have been adopted to study the induced air ow pattern due to obstacle motion. Since experimental measurement is timeconsuming and very expensive, Computational Fluid Dynamics (CFD) techniques have become powerful and e cient tools for studying engineering problems, including air ow and contaminant distribution in enclosures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during the last years, physical activity influence on different kinds of ventilated enclosures was studied, by numerical simulation, by different authors as Matsumoto (Matsumoto et al, 2002Santa Cruz et al, 2007a,b;Mazumdar and Chen, 2007;and Shih et al, 2007. These authors studied the incidence of the motion of a person modeled by a cylinder shape or a box shaped manikin on the airflow distribution and on the impact contaminant transport for different ventilation systems: a diffuser placed on one wall near the ground (Matsumoto et al, 2002 a downstream laminar airflow in an operating room (Santa Cruz et al, 2007a), a ventilated isolation room (Shih et al, 2007) or a ventilated commercial airliner cabin (Mazumdar and Chen, 2007). A limited number of experimental studies dealing with moving objects have been reported.…”
Section: Introductionmentioning
confidence: 99%